Taṭbīq Ṭarīqah Retelling Story Bi ar-Rusūm al-Mutasalsilah Li Tarqiyah Qudrah aṭ-Ṭalabah `Alā Mahārah al-Kalām (Dirāsah Tajrībiyah Bi Bāb an-Najāḥ Banda Aceh) - Nurdiyani Nurdiyani; Buhori Muslim (EL-MAQALAH : Journal of Arabic Language Teaching and Linguistics, 2020)
In the second language, speaking is a basic skill in learning language, because language it selft is speech, a person is not considered of mastered the language except by mastering the speaking. The students of Babun Najah not only found it difficult to speak the Arabic language but got bored as well. Thus, the student had a very low ability. It was caused by the disagreement between methods used by teachers and not using the interesting media according to students’ condition, it made the students feel bored, and lack attention to the subject; even some of them spoke during the teaching and learning process. So the learning process runs ineffectively. This resulted in the limited ability of students to speak Arabic. Based on this problem that has been studied by the researchers, we need for solution to overcome these problems, including: applying the Retelling Story method with the serial images in teaching Arabic language to reach the purposes of teaching speaking skills, in hopes of increasing student ability in speaking skills by combining these two variables. The purpose of this research is to know students’ responses to speaking skills and students' abilities in speaking the Arabic language using the retelling method and serial pictures in Babun Najah Banda Aceh boarding school. Quantitative supported by qualitative approach along with experimental method was used by the researcher. Purposive sampling was used to find the second graders of II-C as a control class and II-D as an experimental class that consisted of 23 students. The results are that students’ response toward the Retelling story Method with the pictures series is well, and the use of the Retelling story Method with the pictures series was effective and it gave a good impact on students of Babun Najah Banda Aceh boarding school, which the result from the t-test relate calculation is greater than t-table result, that is 1,69 < 1,93.